Curse on this country : the rebellious army of imperial Japan - Orbach, Danny (Cornell University Press, 2017)
Imperial Japanese soldiers were notorious for blindly following orders, and their enemies in the Pacific War derided them as 'cattle to the slaughter.' But, in fact, the Imperial Japanese Army had a long history as one of the most disobedient armies in the world. Officers repeatedly staged coups d'états, violent insurrections, and political assassinations; their associates defied orders given by both the government and the general staff, launched independent military operations against other countries, and in two notorious cases conspired to assassinate foreign leaders despite direct orders to the contrary. This work explains the culture of rebellion in the Japanese armed forces.